The role of emotional marketing on instagram in shaping generation z’s purchase intention toward pop culture collectibles - Chu, Hor Yin (2025)
The growth of social media has transformed marketing, particularly in influencing Generation Z, who respond strongly to emotionally engaging and socially interactive content. Instagram, as a visually oriented platform, has become a key channel for promoting pop culture collectibles, which often reflect emotional attachment, identity, and social belonging. Drawing on the Stimulus–Response (S-R) Theory and Commitment-Trust Theory, this study examines how emotional marketing on Instagram shapes Generation Z’s purchase intention toward pop culture collectibles.